2010
DOI: 10.1007/s11999-010-1445-y
|View full text |Cite
|
Sign up to set email alerts
|

Curettage and Cryosurgery for Low-grade Cartilage Tumors Is Associated with Low Recurrence and High Function

Abstract: Background Chondrosarcomas of bone traditionally have been treated by wide or radical excision, procedures that may result in considerable lifelong disability. Grade 1 chondrosarcomas have little or no metastatic potential and are often difficult to distinguish from painful benign enchondromas. Curettage with adjuvant cryosurgery has been proposed as an alternative therapy for Grade 1 chondrosarcomas given the generally better function after the procedure. However, because it is an intralesional procedure, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…The MSTS score after curettage treatment was 99%, better than that in previous studies, which ranged from 90% to 93%. 7,16,21 Two cohort studies showed higher MSTS scores for patients who underwent intralesional curettage than those who underwent wide resection (98% vs. 84% and 89% vs.72%); 12,22 in our study, we had similar results with 99% vs. 94%. Additionally, the MSTS score was significantly different ( p ¼ 0.048) between the two groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The MSTS score after curettage treatment was 99%, better than that in previous studies, which ranged from 90% to 93%. 7,16,21 Two cohort studies showed higher MSTS scores for patients who underwent intralesional curettage than those who underwent wide resection (98% vs. 84% and 89% vs.72%); 12,22 in our study, we had similar results with 99% vs. 94%. Additionally, the MSTS score was significantly different ( p ¼ 0.048) between the two groups.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, some studies are advocated using extended intralesional curettage, which was an option for benign aggressive tumors of bone, for patients with low-grade chondrosarcoma. 12e15 There are several adjuvant methods for extended intralesional curettage, such as phenol application, 13 cauterization, 12,15 or cryotherapy 16 followed by either cementation 17 or bone grafting. Previous studies have demonstrated that these adjuvant treatments are necessary for control of local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, we tried not to biopsy lesions that appeared to be low-grade lipomatous tumours, low-grade cartilaginous tumours, or myxoid, as they are difficult to interpret histologically. 3 Table 4 Accuracy of computed tomography-guided core needle biopsy (CT-guided CNB) and incisional biopsy for bone versus softtissue lesions Table 5 Accuracy of computed tomography-guided core needle biopsy (CT-guided CNB) and incisional biopsy in terms of lesion type lipomatous tumour, well-differentiated liposarcoma, or low-grade chondrosarcoma can be safely treated by marginal resection without biopsy 17,18 or extended intralesional curettage, 19,20 as the risk of recurrence is low. Nonetheless, in indeterminate lesions, biopsy is still recommended.…”
Section: Comparison Of Both Biopsy Methodsmentioning
confidence: 99%
“…Nevertheless, local recurrence of grade 1 CS may present a progression of malignancy with an influence on patient survival [18]. In recent decades, intralesional curettage with local adjuvants and bone filling with either bone grafts or cement has been widely used as surgical treatment of grade 1 CS of the appendicular skeleton [12, 1517, 1922]. On the other hand, in case of an aggressive aspect on imaging and cortical disruption of grade 1 CS, resection with wide margins, following the surgical criteria of primary bone sarcoma, has been recommended [5, 6, 13, 14, 23, 24].…”
Section: Introductionmentioning
confidence: 99%